DETERMINANTS OF STOCK PRICES: CAPITAL STRUCTURE, PROFITABILITY, AND SALES GROWTH - Deden Tarmidi; Hendro Paulus; Apollo Daito; Nurul Hidayah; Muhyarsyah (ZILLZELL MEDIA PRIMA, 2026)
This study analyzes the effect of capital structure, profitability, and sales growth on stock prices, with firm size serving as a moderating variable in property and real estate companies listed on the Indonesia Stock Exchange. The sample was determined using purposive sampling by selecting firms that consistently published complete annual reports and reported positive earnings during the 2020–2023 period, resulting in 26 companies and 104 panel observations that were examined using panel data regression. The results show that capital structure and profitability have a positive and statistically significant influence on stock prices, while sales growth demonstrates a significant negative effect. Furthermore, firm size strengthens the relationship between capital structure and sales growth with stock prices but does not moderate the effect of profitability. These findings support signaling theory by indicating that investor responses to financial indicators are shaped by firm-specific characteristics and provide practical implications for corporate financial policy and investment decision-making in the property and real estate sector.